2015
DOI: 10.1186/s12876-015-0375-2
|View full text |Cite
|
Sign up to set email alerts
|

Reduced lymphocyte count as an early marker for predicting infected pancreatic necrosis

Abstract: BackgroundEarly occurrence of immunosuppression is a risk factor for infected pancreatic necrosis (IPN) in the patients with acute pancreatitis (AP). However, current measures for the immune systems are too cumbersome and not widely available. Significantly decreased lymphocyte count has been shown in patients with severe but not mild type of AP. Whereas, the correlation between the absolute lymphocyte count and IPN is still unknown. We conduct this study to reveal the exact relationship between early lymphocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 22 publications
3
29
0
Order By: Relevance
“…Multivariate stepwise logistic analysis showed that sPD-L1 levels and lymphocyte count were independently associated with the development of infectious complications in AP. This is consistent with a previous study showing that reduced lymphocyte count within 48 h of AP onset were independently associated with the development of infected pancreatic necrosis [33]. Pronounced downregulation of HLA-DR expression was also seen in patients who had AP with infectious complications.…”
Section: Discussionsupporting
confidence: 92%
“…Multivariate stepwise logistic analysis showed that sPD-L1 levels and lymphocyte count were independently associated with the development of infectious complications in AP. This is consistent with a previous study showing that reduced lymphocyte count within 48 h of AP onset were independently associated with the development of infected pancreatic necrosis [33]. Pronounced downregulation of HLA-DR expression was also seen in patients who had AP with infectious complications.…”
Section: Discussionsupporting
confidence: 92%
“…Neutrophils and lymphocytes are important components of the WBCs and high levels of neutrophil count are associated with a more pronounced inflammatory state. Several investigators also have demonstrated a significant decrease of lymphocyte count in SAP is significantly and independently associated with the development of AP 20 , 21 . Additionally, an elevated neutrophil count with a concomitant decreased lymphocyte count has been associated with bacteremia and sepsis but no differece of WBC count 12 , 22 .…”
Section: Discussionmentioning
confidence: 94%
“…In a study by Shen et al, the lymphocyte count was significantly associated with the development of infected pancreatic necrosis. 32 The pre-operative lymphocyte count was also evaluated in patients with adnexal torsion and several studies showed no significant diagnostic value. 29 According to our study, pre-operative lymphocyte count was lower in the torsion group compared to the non-torsion group, but it was higher in the infarction group than the non-infarction group.…”
Section: Discussionmentioning
confidence: 99%